Phase transitions in antiferromagnetic superlattices - Carriço, Artur da Silva (2020)
We investigate the temperature dependence of the magnetization of films and superlattices of uniaxial antiferromagnets using a self-consistent, mean-field approach and apply the theory to FeF2/CoF2 superlattices. The number of magnetic phase transitions in this system (one or two) depends on the thicknesses of the films in the superlattice and on the interface exchange constant. Weak interface coupling leads to two transitions as do thick films. Our findings are in good agreement with recent experimental results and indicate that the FeF2/CoF2 system displays strong interface coupling.